Research Review on the Applicability of Blood Flow Restriction Combined with Low - intensity Resistance Training for Half - Marathon Runners - Xiao, Junjie (International Journal of Public Health and Medical Research, 2026)
Driven by the dual strategies of national fitness and building a sports - power country, the half - marathon sport is developing in a large - scale and professional manner. The group of popular elite half - marathon runners is constantly growing. However, this group generally faces problems such as good aerobic capacity but insufficient lower - limb strength and speed ability, fragmented training time, and a high risk of injury from high - intensity strength training. Blood flow restriction combined with low - intensity resistance training (LL - BFRT), characterized by "low load, high neuromuscular adaptation", can enhance muscle strength without the need for professional equipment, providing a new approach to address the training pain points of popular elite half - marathon runners. This paper reviews the mechanism of action of LL - BFRT, its research status at home and abroad, analyzes the theoretical basis and practical adaptability of LL - BFRT for this group in combination with the specific characteristics of the half - marathon sport, explores the key points of its application scheme design, and finally points out the current research deficiencies and future directions. The aim is to provide a theoretical reference for the application of LL - BFRT in half - marathon training.